2019
DOI: 10.1109/access.2019.2900118
|View full text |Cite
|
Sign up to set email alerts
|

Robust Feature Selection With LSTM Recurrent Neural Networks for Artificial Immune Recognition System

Abstract: Stability and robustness of feature selection techniques have great importance in the high dimensional and small sample data. The neglected subject in the feature selection is solving the instability problem. Therefore, an ensemble gene selection framework is used in order to provide stable and accurate results of feature selection algorithms. Sequence modeling from high-dimensional data is an important research area for the discovery of biomarkers. Identifying biomarkers requires robust gene selection methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Generally, IDT can improve the effectiveness of supply chain management decision-making, such as optimizing supply chain processes and saving decision costs. However, when decisions must be made using incomplete data or artificial intelligence algorithms must be performed through rapid iterations, IDT may generate unreasonable or deviated decisions (Sahin and Diri, 2019). Therefore, supply chain enterprises should pay attention to technology risks when using IDT and strive to improve the robustness of big data algorithms (Metcalf et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, IDT can improve the effectiveness of supply chain management decision-making, such as optimizing supply chain processes and saving decision costs. However, when decisions must be made using incomplete data or artificial intelligence algorithms must be performed through rapid iterations, IDT may generate unreasonable or deviated decisions (Sahin and Diri, 2019). Therefore, supply chain enterprises should pay attention to technology risks when using IDT and strive to improve the robustness of big data algorithms (Metcalf et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Şahín and Diri [43] showed that accuracy of feature selection can be further improved by applying regularization and variable selection using Elastic Net as verified by Zou and Hastie [25] for the DKT model, with LSTM [44], [45] then showing strong performance in time series data.…”
Section: Knowledge Tracingmentioning
confidence: 95%
“…This approach leverages deep learning to analyze functional spectra, quantifying the activities of biological pathways for precise and effective cancer subtype classification. D. Q. Zeebaree, H. Haron, and A. M. Abdulazeez [35] Proposed a new approach that revolves around modeling enduring unit cells through Long Short-Term Memory (LSTM). LSTM, a subtype of Recurrent Neural Network (RNN) within the realm of Artificial Neural Networks (ANN), is a suitable framework.…”
Section: Literature Reviewmentioning
confidence: 99%